A robust phylogenomic framework for the calamoid palms - Kuhnhäuser, BG; Bellot, S; Couvreur, TLP; Dransfield, J; Henderson, A; Schley, R; Chomicki, G; Eiserhardt, WL; Hiscock, SJ; Baker, WJ (Elsevier, 2021)
Well-supported phylogenies are a prerequisite for the study of the evolution and diversity of life on earth. The subfamily Calamoideae accounts for more than one fifth of the palm family (Arecaceae), occurs in tropical rainforests across the world, and supports a billion-dollar industry in rattan products. It contains ca. 550 species in 17 genera, 10 subtribes and three tribes, but their phylogenetic relationships remain insufficiently understood. Here, we sequenced almost one thousand nuclear genomic regions for 75 systematically selected Calamoideae, representing the taxonomic diversity within all calamoid genera. Our phylogenomic analyses resolved a maximally supported phylogenetic backbone for the Calamoideae, including several higher-level relationships not previously inferred. In-depth analysis revealed low gene tree conflict for the backbone but complex deep evolutionary histories within several subtribes. Overall, our phylogenomic framework sheds new light on the evolution of palms and provides a robust foundation for future comparative studies, such as taxonomy, systematics, biogeography, and macroevolutionary research.